The search for democratic renewal : the politics of consultation in Britain and Australia - Manwaring, Rob (Manchester : Manchester University Press, 2014)
Why is the search for democratic renewal so elusive? This book examines both the political and policy implications of efforts by the centre-left to transform democracy. This is a story not only about democratic change, but also the identity crisis of centre-left political parties.
Cover; The search for democratic renewal; Contents; List of Figures and tables; Acknowledgements; 1 Labour in flux; 2 Labour, democratic renewal and the New Social Democracy; 3 Understanding political participation; 4 Political participation: continuity and change; 5 New Social Democratic governments in Britain and Australia; 6 National conversations; 7 Engagement at the regional level; 8 Beyond the glittering facade; References; Index.
Online resource; title from PDF title page (EBSCO, viewed December 30, 2015).
Includes bibliographical references and index.
In English.
JSTOR
Keywords: Labour Party (Great Britain) -- History; Australian Labor Party -- History; Australian Labor Party; Labour Party (Great Britain); Democracy -- Great Britain; Democracy -- Australia; Political participation -- Great Britain; Political participation -- Australia; Great Britain -- Politics and government; Australia -- Politics and government; Participation politique -- Grande-Bretagne.; Participation politique -- Australie; Grande-Bretagne -- Politique et gouvernement; Australie -- Politique et gouvernement; Socialism and left-of-centre democratic ideologies; POLITICAL SCIENCE -- Political Ideologies -- Communism, Post-Communism & Socialism; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Democracy; Political participation; Politics and government; Australia; Great Britain; Demokrati; Politiskt deltagande; Politiska förhållanden.; Historia; Society & Social Sciences -- Politics & government -- Political ideologies; History